2014
DOI: 10.1111/ibi.12192
|View full text |Cite
|
Sign up to set email alerts
|

Lek fidelity and movement among leks by male Greater Sage‐grouseCentrocercus urophasianus: a capture‐mark‐recapture approach

Abstract: Males in lek mating systems tend to exhibit high fidelity to breeding leks despite substantial evidence of skewed mating success among males. Although movements between leks are often reported to be rare, such movements provide a mechanism for an individual to improve lifetime fitness in response to heterogeneity in reproductive conditions. Additionally, estimates of apparent movements among leks are potentially biased due to unaccounted variation in detection probability across time and space. We monitored br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 66 publications
1
46
2
Order By: Relevance
“…Quad = quadratic constraint applied across within‐year interval transition probabilities. N = estimated male population size (Gibson et al ). Age 2 = quadratic relationship of minimum hen age.…”
Section: Resultsmentioning
confidence: 99%
“…Quad = quadratic constraint applied across within‐year interval transition probabilities. N = estimated male population size (Gibson et al ). Age 2 = quadratic relationship of minimum hen age.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research observed 15–27% of adult males on ≥2 leks (Wallestad and Schladweiler , Emmons and Braun , Dunn and Braun ), and reported a 3% chance annually a male would move from the lek where it was captured (Gibson et al ). Our estimates were likely higher because we knew where each bird was daily, whereas other studies relied on very high frequency telemetry (Wallestad and Schladweiler , Emmons and Braun , Dunn and Braun ) and resighting and recapturing banded birds (Gibson et al ), which would result in substantially fewer opportunities to observe male sage‐grouse interlek movements. Although we observed wide credible intervals around our seasonal interlek movement estimates (e.g., 95% CI = 0.081–0.686 for 2014), we believe the estimates are reasonable because 67% of the male‐sage‐grouse population never moved among leks, and 33% of males moved among leks, sometimes >10 times.…”
Section: Discussionmentioning
confidence: 98%
“…These factors may enhance the successful breeding of sage‐grouse at leks in unburned islands. Although movement between leks is uncommon (e.g., Fremgen et al, ; Gibson, Blomberg, Atamian, & Sedinger, ), male sage‐grouse may experience lower lek fidelity in disturbed and fragmented landscapes as compared to intact habitats (Foster et al, ; Schroeder & Robb, ). As a result, the apparent high persistence within unburned islands may also be partly caused by postfire movements of male sage‐grouse from burned leks to unburned island leks.…”
Section: Discussionmentioning
confidence: 99%